Systems Biology approach for the identification of neurotransmission and synaptic risk genes and disrupted biological processes in Autism Spectrum Disorder - Vilela, Joana (2021)
The objective of this study is the identification of Single Nucleotide Variants (SNVs) in neurotransmission and synaptic genes (NS genes) that play a role in ASD etiology, and the biological processes and global networks affected.